Functional metasurfaces based on metallic and dielectric subwavelength slits and stripes array. (13th March 2018) - Guo, Yinghui; Pu, Mingbo; Li, Xiong; Ma, Xiaoliang; Gao, Ping; Wang, Yanqin; Luo, Xiangang
Abstract: Starting with the early works of extraordinary optical transmission and extraordinary Young's interference, researchers have been fascinated by the unusual optical properties displayed by metallic holes/slits and subsequently found similar abnormities in dielectric counterparts. Benefiting from the shrinking wavelength of surface plasmon polaritons excited in metallic slits and high refractive index of dielectric stripes, one can realize local phase modulation and approach desired dispersion by engineering the geometries of a slits and stripes array. In this review, we review recent developments in functional metasurfaces composed of various metallic and dielectric subwavelength slits and stripes arrays, with special emphasis on achromatic, ultra-broadband, quasi-continuous, multifunctional and reconfigurable metasurfaces. Particular attention is paid to provide insight into the design strategies for these devices. Finally, we give an outlook of the development in this fascinating area.